A Review on Applications of IoT in Heating, Ventilation, Air Conditioning and its Control - Bagsiraj, M. Kaif R.; Narwade, Shahid R.; Pirjade, Khalid S.; Husainy, Avesahemad S. N. (Asian Review of Mechanical Engineering, 2021)
In this review paper it is discussed about how an IoT can be implemented in the refrigeration and air conditioning to save the energy at different climatic problem. We will be discussing about the knowledge of sensor, actuators, and other objects which are connected to Internet and application of IoT. While using IoT in the application it will sense the different parameter like temperature, voltage etc. and maintain the feasible condition in order to save the human time. Now-a-days industries are also using IoT to get the better results. The use of IoT is implemented in industry as well as for household purpose. In this paper, the brief description about the application of IoT in different climatic conditions and how it is beneficial for the human comfort and also how it can reduce the wastage of energy.